2023
DOI: 10.1080/19932820.2023.2281116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fullerene C60 on liver tissue in liver ischemia reperfusion injury in rats undergoing sevoflurane anesthesia

Aydın Yavuz,
Ayca Tas Tuna,
Cagrı Ozdemir
et al.

Abstract: This study aimed to investigate the effects of fullerene C60 on rat liver tissue in a liver ischemia reperfusion injury (IRI) model under sevoflurane anesthesia to evaluate the ability of nanoparticles to prevent hepatic complications. A total of 36 adult female Wistar Albino rats were divided into six groups, each containing six groups as follows: sham group (Group S), fullerene C60 group (Group FC60), ischemia-reperfusion group (Group IR), ischemia-reperfusion-sevoflurane group (Group IR-Sevo), ischemia-repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…We have previously shown, that water-soluble C 60 fullerenes prevent the restraint of stress-induced oxidative disorders in rat' brain and heart tissues [ 8 ] as well as an acute liver injury [ 9 ], diminish muscle fatigue in rats [ 10 ], markedly decrease the level of oxidative stress in diet-induced obesity rats [ 11 ] and, finally, realize therapeutic effects in the models of muscle injury and ischemia of the muscle soleus in rats [ 12 , 13 ]. Recenly the authors [ 14 , 15 ] demonstrated the protective effect of C 60 fullerene on liver tissue in liver ischemia reperfusion injury as well as on lung and renal tissue in lower extremity ischemia-reperfusion injury in rats, which opens up a prospect for its use in biomedicine.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown, that water-soluble C 60 fullerenes prevent the restraint of stress-induced oxidative disorders in rat' brain and heart tissues [ 8 ] as well as an acute liver injury [ 9 ], diminish muscle fatigue in rats [ 10 ], markedly decrease the level of oxidative stress in diet-induced obesity rats [ 11 ] and, finally, realize therapeutic effects in the models of muscle injury and ischemia of the muscle soleus in rats [ 12 , 13 ]. Recenly the authors [ 14 , 15 ] demonstrated the protective effect of C 60 fullerene on liver tissue in liver ischemia reperfusion injury as well as on lung and renal tissue in lower extremity ischemia-reperfusion injury in rats, which opens up a prospect for its use in biomedicine.…”
Section: Introductionmentioning
confidence: 99%